Auctioning IT Contracts with Renegotiable Scope - Huang, He; Li, Zhipeng; Liu, De; Xu, Hongyan (Management Science, 2022)
Motivated by challenges facing IT procurement, this paper studies a hybrid procurement model in which a reverse auction of a fixed-price IT outsourcing contract may be followed by renegotiation to extend the contract’s scope. In this model, the buyer balances the needs to incentivize noncontractible vendor investment and to curb the winning vendor’s information rent by choosing the initial project scope and the buyer’s investment in the quality of the project. We find that a buyer may benefit from inducing ex post renegotiation to motivate vendor investment, especially when the winning vendor has high bargaining power and the quality uncertainty is low. Broadening the initial scope reduces information rent but leaves little room for ex post renegotiation and, hence, discourages vendor investment, whereas increasing the buyer’s investment has opposite effects. Interestingly, the two measures can be strategic substitutes or complements depending on the likelihood of the renegotiation and the two parties’ bargaining powers. The buyer may strategically set a low initial project scope and high investment to incentivize renegotiation and vendor investment, which may explain why many IT outsourcing projects start small and allow expansions. Our findings also generate several testable predictions for IT outsourcing. This paper was accepted by Kartik Hosanagar, information systems.